The Effectiveness of Interactive Digital Platforms in Improving Academic Outcomes: A Systematic Literature Review - Dina Rahayu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the effectiveness of interactive digital platforms in improving student academic outcomes. The integration of digital platforms in education is becoming increasingly important, but challenges arise regarding educators' adaptation of technology. This study analyzes the effectiveness of platforms such as Kahoot and Padlet through a systematic literature review. The study identifies gaps in previous research that focused more on platform features than on learning outcomes and educator adaptation. Using a systematic literature review of 45 peer-reviewed articles (2019-2024), this study explores the relationship between platform interactivity, educator technology proficiency, and measurable academic improvement. Data analysis uses thematic coding to identify patterns in successful digital learning implementation. The results show that interactive platforms can improve academic performance by 15-25% if educators have adequate technological skills, but success rates decline without proper training. This study proposes a comprehensive framework that integrates platform effectiveness metrics with educator development strategies. Recommendations include structured technology training programs and standardized assessment protocols to measure the effectiveness of digital learning.